2020
DOI: 10.3389/fnins.2020.00594
|View full text |Cite|
|
Sign up to set email alerts
|

The Potential of Functional Near-Infrared Spectroscopy-Based Neurofeedback—A Systematic Review and Recommendations for Best Practice

Abstract: Background: The effects of electroencephalography (EEG) and functional magnetic resonance imaging (fMRI)-neurofeedback on brain activation and behaviors have been studied extensively in the past. More recently, researchers have begun to investigate the effects of functional near-infrared spectroscopy-based neurofeedback (fNIRS-neurofeedback). FNIRS is a functional neuroimaging technique based on brain hemodynamics, which is easy to use, portable, inexpensive, and has reduced sensitivity to movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 132 publications
0
101
0
3
Order By: Relevance
“…The RAP dataset is closer to previous EEG experiments (Cavazza et al, 2014) and the one with perhaps the most potential for confounding various aspects of PFC asymmetry in terms of its dimensional interpretation (approach, valence). On the other hand, it has some of the longest fNIRS NF epochs (Kohl et al, 2020) and is a good candidate to study signal dynamics.…”
Section: Time Series Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The RAP dataset is closer to previous EEG experiments (Cavazza et al, 2014) and the one with perhaps the most potential for confounding various aspects of PFC asymmetry in terms of its dimensional interpretation (approach, valence). On the other hand, it has some of the longest fNIRS NF epochs (Kohl et al, 2020) and is a good candidate to study signal dynamics.…”
Section: Time Series Discussionmentioning
confidence: 99%
“…In this section, we are briefly discussing the relevance and potential community interest of our datasets, considering the increasing popularity of fNIRS and in particular fNIRS NF. We will be basing this discussion primarily on the recent review of fNIRS NF by Kohl et al (2020), which collected a significant FIGURE 2 | (A) Overview of the apparatus used in our experiments: fNIR Optical Brain Imaging System (fNIR400) by Biopac Systems with one PC dedicated to the data acquisition, and one PC dedicated to running the simulation and visualization of the stimulus presented in real-time to the subjects. (B) The 16-channel sensor placed on the subjects' forehead (C) showing the selected channels for the calculation of the asymmetry values.…”
Section: Representativity and Interest Of The Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…While recently published studies support the potential of f NIRS-neurofeedback for clinical and non-clinical applications, a recent systematic review concluded that sufficiently powered studies and large randomized controlled trials are still lacking and specificity of the reported effects remains to be demonstrated ( Kohl et al, 2020 ). Also, shortcomings in reporting important information were identified.…”
Section: Optical Brain Imaging and Its Application To Neurofeedbackmentioning
confidence: 99%